A carta de reclamação na Facebook: uma proposta para aulas de língua portuguesa - Batista, Juliana de Fátima (2016)
In attempt to bring together the technology with the teaching of Portuguese, and with a view to reduce the difficulties and the lack of interest of the students for the writing, we presented a propose to work with the gender letter of complaint. Considering the difficulties of the students in the place of producers of texts and their high interest by the relations established in the social networks, with our experience, we tried to provide the inclusion of learners in reading, writing and rewriting experience socially located and also using the digital support Facebook to publish it. Therefore, the objective, which guided our research, was the contribution with the development of the writing capacity, the critical and citizen formation of the students of 9° year of Elementary School in a public school of Araguari - M.G. - Brazil, using the elaboration and the application of diversified activities in the classroom. At the same time, it was important for us to take advantage of our experience to present to the teachers a suggestion to make it easier and stimulate the work with this gender. In this way, the rout chosen to propose the production of a letter of complaint was the elaboration of a pedagogical sequence, using, for this, the structure proposed by Dolz, Noverraz and Schneuwly (2004), considering the class to application of the available resources in the school until the end of 2015. For this, we considered the theoretical contributions of researchers as Bakhtin (2011), Marcuschi (2008), Dolz and Schneuwly (2004), Barbosa (2005), Barbosa and Rovai (2012), Rojo (2005; 2009; 2012) and Rojo and Barbosa (2015), mainly. In terms of methodology, we identify with the features of research action described by Souza, Hudson and Pinheiro (2007). In the development of the structure proposed by Dolz, Noverraz and Schneuwly (2004) were considered, in all proposed modules, the knowledge about the subject content, the stile and the compositional construction, as Bakhtin (2011), of letter of complaint. Taking the achieved results in consideration, we verified that the application of the pedagogical sequence meant to domain of the gender letter of complaint, when properly mediated by the teacher, contribute with the development of the writing capacity, the critical and citizen formation of the students concerned in the production.